Exploring the Psychological Cognitive Characteristics and Artistic Healing Pathways of the Group with Suspected Illness Anxiety - Wang, Xiangping (Transactions on Social Science, Education and Humanities Research, 2026)
As a core subtype of health anxiety, hypochondriacal anxiety refers to a psychological disorder in which individuals excessively worry about suffering from serious illnesses for a long time, leading to disastrous interpretations of their physical feelings, and accompanied by compulsive behaviors such as repeated medical visits and examinations. At present, research on hypochondriacal anxiety in China is still in its infancy, and there are significant gaps in both theoretical systems and intervention paradigms. This article takes Salkovskis and Warwick's cognitive theory of health anxiety as the core framework, systematically analyzing the psychological and cognitive characteristics of the anxiety group, including four core dimensions: somatic perception bias, catastrophizing thinking, cognitive avoidance and safe behavior, and dysfunctional health beliefs; By combining the core mechanisms of nonverbal expression, symbolic transformation, and emotional regulation in art therapy, this study explores an art therapy path that is suitable for individuals with anxiety disorders. A four stage intervention model of "cognitive awareness emotional externalization cognitive reconstruction behavioral activation" is constructed to provide theoretical reference and practical basis for clinical intervention of anxiety disorders.
Keywords: Hypochondriasis; Cognitive-behavioural Model; Art Healing; Doubtful illness anxiety.